Eating disorder pathology in elite adolescent athletes - Giel, Katrin; Diehl, Katharina; Schneider, Sven (The international journal of eating disorders, 2016)
Objective We aimed to investigate eating disorder pathology in German elite adolescent athletes. Evidence suggests that eating disorder pathology is more common in adult elite sports, especially in female athletes and in sports emphasizing leanness. There is a scarcity of studies in elite adolescent athletes who are in a vulnerable developmental stage and are affected by general as well as sport-specific risk factors. Method Our data was derived from the German Young Olympic Athletes' Lifestyle and Health Management Study (GOAL) which conducted a survey in 1138 elite adolescent athletes. In this sample, we assessed body weight, weight control behavior, body acceptance and screened overall for core symptoms of eating disorders, depression and anxiety. We performed a tree analysis to identify high risk groups for eating disorder pathology. Results High risk groups comprised (a) athletes competing in weight dependent sports, and among athletes competing in disciplines other than weight dependent sports (b) athletes who are high on negative affectivity, (c) female athletes and (d) male athletes competing in endurance, technical or power sports. Athletes competing in weight dependent disciplines reported wide spread use of compensatory behaviors to influence body weight. Athletes reporting eating disorder pathology showed higher levels of depression and anxiety than athletes without eating disorder pathology. Discussion Increased psychosocial burden in athletes with eating disorder pathology suggests that eating disorder symptoms should not be accepted as an unproblematic and functional part of elite sports. The prevention and management of eating disorder pathology is especially important in weight dependent sports. © 2016 Wiley Periodicals, Inc. (Int J Eat Disord 2016; 49:553-562)